Ser-para-a-morte na apropriação de si em Heidegger: pressupostos para a educação - OLIVEIRA, Merynilza Santos de (Universidade Federal do Pará, 2015)
The text presented effective discussion of the main concepts being-toward-death and self-esteem of the philosopher Heidegger's philosophy, based on the book Being and Time, with the aim to understand how the being-toward-death implies ownership of selfesteem. The methodological basis used is that of phenomenology, hermeneutics, created by the author himself to realize their concepts, forming the body of his work. Writing is developed in three chapters. The first is an overview of Heidegger's thought, retracing the route of his philosophizing, explaining the use of concepts through comprehensive explanations, ranging from the self, passing by Dasein, to the being-fordeath ; is also a foundation for the next steps. The second chapter is more strongly beunto- death in the link with the literature, the book "The Death of Ivan Ilyich" by Leo Tolstoy, demonstrating the experience of the character of the settlement itself, to face his dying prematurely after being challenged by anxiety, comprising be-unto-death. In the third chapter a summary of the issues discussed with emphasis on self-esteem, conceiving the Heideggerian concepts such as care, impersonality, chatter, used in understanding education in Heidegger will be taken.